Perindopril improves cardiac fibrosis through targeting the AngII/AT1R pathway: Perindopril improves cardiac fibrosis - Liang, Hao; Zhang, Na; Zhao, Le; Wang, Qingsong; Deng, Shuai; Shen, Jing; Wang, Hong (Cellular and Molecular Biology, 2023)
To uncover the potential effect of Perindopril on cardiac fibrosis caused by pressure overload and the underlying mechanism. Cardiac fibrosis model in mice was established by TAC method. Mice were assigned into sham group, TAC group, 2 mg/kg Perindopril group (Per (2 mg/kg)) and 8 mg/kg Perindopril group (Per (8 mg/kg)). Cardiac structure changes were assessed by measuring HW/BW, HW/TBL, LW/BW and LW/TBL in each group. Echocardiography was performed to assess mouse cardiac function by recording EF, LVIDd, IVSd and LVPWd. Relative levels of fibrosis markers were determined. AngII content was examined by ELISA. Besides, mRNA levels of key genes in the AngII/AT1R pathway were finally detected. TAC induced cardiac insufficiency, left ventricular dilatation, cardiac hypertrophy and myocardial collagen deposition in mice. In addition, fibrosis markers were upregulated in mice of TAC group. Perindopril markedly reversed TAC-induced pathological changes in cardiac structure and function of mice. Meanwhile, Perindopril dose-dependently reversed the upregulated genes in the AngII/AT1R pathway. Perindopril improves cardiac fibrosis induced by pressure overload through activating the AngII/AT1R pathway.